2016
DOI: 10.1167/iovs.16-20049
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Quantification of Choroidal Macrophages in Human Eyes With Age-Related Macular Degeneration

Abstract: PurposeIncreasing evidence suggests a role for macrophages in the pathogenesis of age-related macular degeneration (AMD). This study examined choroidal macrophages and their activation in postmortem eyes from subjects with and without AMD.MethodsChoroids were incubated with anti-ionized calcium-binding adapter molecule 1 (anti-IBA1) to label macrophages, anti-human leukocyte antigen-antigen D-related (anti-HLA-DR) as a macrophage activation marker, and Ulex europaeus agglutinin lectin to label blood vessels. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 43 publications
(47 reference statements)
11
101
2
Order By: Relevance
“…A similar finding has been recently reported in the normal human choroid [65]. Kumar et al [47] were the first to examine the behavior of macrophages in mouse choroid explants using time lapse confocal microscopy and revealed that their cell bodies were rather sessile however their processes exhibited repeated extension and retraction in multiple directions.…”
Section: Distribution and Phenotypesupporting
confidence: 78%
“…A similar finding has been recently reported in the normal human choroid [65]. Kumar et al [47] were the first to examine the behavior of macrophages in mouse choroid explants using time lapse confocal microscopy and revealed that their cell bodies were rather sessile however their processes exhibited repeated extension and retraction in multiple directions.…”
Section: Distribution and Phenotypesupporting
confidence: 78%
“…Macrophages, in particular, seem to play an important role in AMD pathogenesis . In striking similarity to their presence at atherosclerotic blood vessel sites in cardiovascular disease, macrophages are found at the sites of RPE atrophy, breakdown of Bruch's membrane, and choroidal neovascularization .…”
Section: Zinc As Modulator Of Humoral and Cellular Immunity: Implicatmentioning
confidence: 98%
“…Development of choroidal neovascularizations (CNVs) defines the late stage of neovascular age‐related macular degeneration (AMD). Monocytes play an important role as shown in several studies: tissue specimens of neovascular AMD show macrophages in significantly higher number around the lesion, experimental CNV in mice is attenuated in size upon experimental depletion of circulating monocytes, patients with new‐onset neovascular AMD have increased circulating monocytes and retinal injury leads to chemokine secretion to which circulating monocytes are drawn . These monocytes respond to the injury by secreting vascular endothelial growth factor (VEGF) .…”
Section: Introductionmentioning
confidence: 99%